Experiences of Adult Learners Engaged in Blended Learning beyond COVID-19 in Ghana - Biney Isaac Kofi; Azaglo Janet (De Gruyter, 2024)
The COVID-19 pandemic has transformed the educational landscape, making exploration of blended learning (BL) instructional delivery important. Higher education institutions are navigating the effects of the COVID-19 crisis on instructional delivery. Using Accra Learning Centre as a case study, this article explores the experiences of adult learners engaged in BL after the COVID-19 crisis in Ghana. A qualitative research method was employed, and a purposive sampling procedure was used to select 15 adult learners. An in-depth interview guide was developed to garner data. Thematic, narrative, and interpretivist analytical approaches were adopted in presenting the results. Participants' voices, experiences, and meanings were sought. It emerged that BL promotes inquiry-based, self-directed, and constructivist learning rather than using conventional face-to-face teaching and learning, though conventional teaching and learning cannot be discounted, BL fosters self-paced learning among adult learners. It recommends that faculty continue to sharpen their skills in BL instructional delivery and adult learners should be equipped with skills in time management, and effective digital tools used to engage in BL.